2023
DOI: 10.1111/inm.13235
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of emotional intelligence: A scoping review of emotional intelligence training programme among nurses

Monalisa Saikia,
Linu Sara George,
Bhaskaran Unnikrishnan
et al.

Abstract: The stressful environment of any healthcare setting can be detrimental to nurses' mental and emotional health. In recent years, emotional intelligence (EI) has emerged as a vital psychological resource that positively impacts mental and emotional health and improves organizational functioning and success. This scoping review aimed to collate, synthesize and outline the research conducted on EI training programmes among nurses to assess their effectiveness in improving staff nurses' EI. Electronic databases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Emotional intelligence is crucial for enhancing nurses’ psychological wellbeing because those with higher emotional intelligence are better equipped to handle demanding work environments (Lee & Sim, 2021 ). Interventions targeting emotional intelligence have proven effective in bolstering nurses’ psychological resources and their ability to manage work-related stress (Liu et al, 2023 ; Saikia et al, 2023 ). The relationship between gender and secondary traumatic stress remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence is crucial for enhancing nurses’ psychological wellbeing because those with higher emotional intelligence are better equipped to handle demanding work environments (Lee & Sim, 2021 ). Interventions targeting emotional intelligence have proven effective in bolstering nurses’ psychological resources and their ability to manage work-related stress (Liu et al, 2023 ; Saikia et al, 2023 ). The relationship between gender and secondary traumatic stress remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The literature presents mixed evidence regarding the impact of EI training on learning. Some studies have found a positive impact of EI training on training outcomes, including learning skills, abilities, and knowledge [3,[116][117][118][119][120][121]. In addition, some experimental studies have demonstrated that EI training positively affects experimental groups.…”
Section: Hypothesis Development 221 Emotional Intelligence Training O...mentioning
confidence: 99%
“…In the literature, some studies reported a positive impact of EI training on training outcomes, including learning skills, abilities, and knowledge [3,[116][117][118][119][120][121]. Regarding the effect of learning on training transfer, Baldwin and Ford's [28] model explains that learning and retention are considered the determinants of training transfer (generalization and maintenance).…”
Section: Mediation Of Learningmentioning
confidence: 99%
“…EI is defined as the ability to self-regulate and recognize personal emotions while also responding to others' feelings in an empathetic fashion and developing coping skills that are effective during times of conflict and stress. 4 Some experts assert that EI includes 4 abilities: (1) identifying emotions in oneself and others (self-awareness and awareness of others); (2) self-management; (3) social awareness; and (4) relationship management. 5 High levels of EI are needed during nursing care encounters, particularly because patients and families are often suffering because of physical, spiritual, emotional, and psychological distress.…”
mentioning
confidence: 99%
“…When people have deficient or inadequate EI, they are less likely to correctly or appropriately recognize or understand emotions. 4 A study of Spanish nurses (N = 125) found that EI may help to protect the nurse from the adverse effects of psychosomatic complaints and burnout while also enhancing nurses' job satisfaction. 6 A scoping review of available EI research that included interventions designed to enhance nurses' EI describes variable strategies that focused on outcomes that included anxiety, coping methods, perceived stress levels, and other results of interest.…”
mentioning
confidence: 99%